Elastoplastic deformation and damage process in duplex stainless steels studied using synchrotron and neutron diffractions in comparison with a self-consistent model. (June 2016) - Baczmański, A.; Zhao, Y.; Gadalińska, E.; Le Joncour, L.; Wroński, S.; Braham, C.; Panicaud, B.; François, M.; Buslaps, T.; Soloducha, K.
Abstract: In situ time of flight neutron diffraction and X-ray synchrotron diffraction methods were applied to measure lattice strains in duplex steels during a tensile test. The experimental results were used to study slips on crystallographic planes and the mechanical effects of damage occurring during plastic deformation. For this purpose the prediction of an elastoplastic self-consistent model was compared with the experimental data. The used methodology allowed to determine the elastic limits and parameters describing work hardening in both phases of studied polycrystalline materials. In the second part of this work the developed elastoplastic model was applied to study damage occurring in the ferritic phase. The theoretical results showed a significant reduction of stresses localized in the damaged phase (ferrite) and confirmed the evolution of the lattice strains measured in the ferritic and austenitic phases. Highlights: Neutron and synchrotron diffraction was used during in situ tensile test. Diffraction data were analyzed using self-consistent model. In the frame of self-consistent model ductile damage was predicted. In aged duplex steel damage process is initiated in the ferritic phase. Parameters describing damage in ferritic phase were determined.